World bank financing of education : lending, learning and development / Phillip W. Jones. - Jones, Phillip W. (Phillip Worner), 1949- (Routledge, 2007)
Based on detailed analysis of thousands of confidential World Bank documents, this book demonstrates that the World Bank lies at the centre of the major changes in global education of our time. It outlines the evolution of World Bank lending policies in education, and assesses the policy impact of the Bank's educational projects, looking at how it has: shaped the economic and social policies of many governments, including policies that affect education been an influential proponent of the rapid expansion of formal education systems around the world, financing much of th.